A sensitive fluorescence method for sequence-specific recognition of single-stranded DNA by using glucose oxidase. Issue 13 (4th June 2015) - Li, Yubin; Zhang, Hong; Zhu, Houya; Ling, Liansheng
Abstract : A sensitive fluorescence method was developed for sequence-specific recognition of single-stranded DNA on the surface of silver-coated glass by means of the amplification properties of glucose oxidase. Abstract : A sensitive fluorescence method was developed for sequence-specific recognition of single-stranded DNA on the surface of silver-coated glass. Oligonucleotide 5′-HS-(T)18 -CGT CGC ATT CAG GAT-3′ (Oligo-1) was designed to assemble on the surface of silver-coated glass and acted as capture DNA, and Oligonucleotide 5′-TCT CAA CTC GTA GCT-(T)18 -biotin-3′ was designed as signal DNA (Oligo-2). Upon addition of target DNA (5′-AGC TAC GAG TTG AGA ATC CTG AAT GCG ACG-3′, Oligo-3), signal DNA could bind on the surface of silver-coated glass because of DNA hybridization. The biotin groups on Oligo-2 are then coated with streptavidin, and biotin labeled glucose oxidase (biotin-GOx) is added to bind to streptavidin. The quantity of GOx immobilized in this way is directly related to the quantity of target DNA bound on the surface. Following cleavage of the aptamer with DNase I, glucose is added and oxidized by GOx to yield H2 O2 . Horseradish peroxidase is added and causes the oxidation of 3- p -hydroxyphenylpropanoic acid to yield a fluorescent product. The intensity of the fluorescence is directly related to the target DNA concentration in the range of 25 pM to 5500 pM, and the detection limit was 7 pM. The assay had good sequence selectivity.